A tiered approach to inpatient psychosocial screening in an adult UK burns service. Issue 3 (May 2022) - Shepherd, L.; Beveridge, A.
Highlights: This paper describes a tiered approach to psychosocial screening in a UK service. 95% of patients received some level of input from the burns clinical psychology team. Around three quarters were screened face-to-face by a psychosocial professional. Having a range of psychosocial professionals may be resource- and cost-effective. Psychosocial screening should be a tiered approach and guide intervention. Abstract: National guidance in the UK advises that psychosocial screening is completed for all inpatients admitted to burns services for over 24 h. Acceptable methods of psychosocial screening have been nationally agreed. However, little is known about how different services conduct psychosocial screening. Moreover, data related to validity and reliability are lacking. This paper describes a tiered approach to inpatient psychosocial screening in a UK adult burns service and considers implications for services. Data collected over a seven-year period was analysed retrospectively. Of 891 patients, almost half (48%; n = 431) were screened face-to-face by a graduate level assistant psychologist. Almost one quarter (23%, n = 205) were screened face-to-face by a qualified clinical psychologist. Around a fifth (22%, n = 193) were screened indirectly through psychological discussions at multi-disciplinary team meetings with a member of the burns clinical psychology team present. A minority of patients were screened face-to-face by liaison psychiatry, or by both liaison psychiatry and a clinical psychologist. Screening and delivery of low-level psychological interventions by a graduate level assistant psychologist appeared to protect resources of qualified clinical psychologists for the most distressed patients. Results highlight the value and cost-effectiveness of a tiered approach to psychosocial screening and in guiding subsequent intervention. Future study is needed in relation to inpatient psychosocial screening and its validity and reliability. Investigating the predictive value of screening methods in identifying those with longer-term psychological difficulties would also be important clinically.